2024
DOI: 10.1021/acschembio.3c00750
|View full text |Cite
|
Sign up to set email alerts
|

On the Question of CO’s Ability to Induce HO-1 Expression in Cell Culture: A Comparative Study Using Different CO Sources

Xiaoxiao Yang,
Qiyue Mao,
Binghe Wang

Abstract: With the recognition of the endogenous signaling roles and pharmacological functions of carbon monoxide (CO), there is an increasing need to understand CO's mechanism of actions. Along this line, chemical donors have been introduced as CO surrogates for ease of delivery, dosage control, and sometimes the ability to target. Among all of the donors, two ruthenium− carbonyl complexes, CORM-2 and -3, are arguably the most commonly used tools for about 20 years in studying the mechanism of actions of CO. Largely ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…None of our results support the feasibility of uncatalyzed CO insertion into a hydrazone double bond as a way to sense CO. Just as important to demonstrate the improbable nature of the originally proposed CO-insertion reaction, the problems associated with ruthenium-based CORMs (and some other CORMs) as CO surrogates should also be emphasized. It is important to note that four independent laboratories have shown that these ruthenium–carbonyl complexes do NOT produce a meaningful amount of CO in buffer and cell culture media unless there is an added nucleophile, sodium dithionite. ,,,, The case study described here is another example that these ruthenium-based CORMs (CORM-2 and CORM-3) should not be used to study CO biology or CO chemistry and should not be used to further develop new CO probes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…None of our results support the feasibility of uncatalyzed CO insertion into a hydrazone double bond as a way to sense CO. Just as important to demonstrate the improbable nature of the originally proposed CO-insertion reaction, the problems associated with ruthenium-based CORMs (and some other CORMs) as CO surrogates should also be emphasized. It is important to note that four independent laboratories have shown that these ruthenium–carbonyl complexes do NOT produce a meaningful amount of CO in buffer and cell culture media unless there is an added nucleophile, sodium dithionite. ,,,, The case study described here is another example that these ruthenium-based CORMs (CORM-2 and CORM-3) should not be used to study CO biology or CO chemistry and should not be used to further develop new CO probes.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that four independent laboratories have shown that these ruthenium–carbonyl complexes do NOT produce a meaningful amount of CO in buffer and cell culture media unless there is an added nucleophile, sodium dithionite. 14 , 33 , 34 , 44 , 45 The case study described here is another example that these ruthenium-based CORMs (CORM-2 and CORM-3) should not be used to study CO biology or CO chemistry and should not be used to further develop new CO probes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon monoxide (CO) is primarily considered to be explosive and have mammalian toxicity. , Nevertheless, recent studies revealed that CO can be generated endogenously by heme oxygenase (HO) in the heme of the human body and act as an important gasotransmitter in various physiological and pathological processes. The level of CO in cells and blood is always altered by pathological syndromes, such as lung disease, septicemia, diabetes, and cancer. , Thus, the real-time monitoring of CO in living cells and blood is an important alternative to diagnose a variety of diseases. Despite advances in CO detection, convenient and functional monitoring methods are still urgent to be developed. …”
Section: Introductionmentioning
confidence: 99%